IMPLEMENTATION OF THE KMB DIGITAL EDUCATION APPLICATION ON COMPLIANCE AND WOUND HEALING OF POST-ABDOMINAL SURGERY PATIENTS AT PEMANGKAT REGIONAL HOSPITAL - Ardhana, Putra; Lautan, Lydia Moji; Presty, Marsela Renasari; Pipin, Apriliana; Pramulya, Asmaurina; Kristian, Eben Haezar (Nurse and Health: Jurnal Keperawatan, 2025)
Background: Health education is a crucial component in improving patient adherence to wound care, particularly among individuals recovering from abdominal surgery. Improper wound care can increase the risk of infection and delay the healing process. The integration of digital technology in healthcare provides innovative solutions for patient education. The KMB Digital Education Application serves as a medium to enhance patients’ understanding of postoperative wound management, enabling them to follow care instructions more consistently and achieve faster recovery. Objectives: This study aimed to determine the effect of the KMB Digital Education Application on patient adherence and wound healing among post-abdominal surgery patients at Pemangkat Regional Hospital. Methods: This research employed a quasi-experimental design with a pretest-posttest control group approach. A total of 50 post-abdominal surgery patients were selected using purposive sampling and divided equally into intervention and control groups. The intervention group received education through the KMB Digital Application, while the control group received standard education. Data were collected using observation sheets and analyzed using Repeated Measure ANOVA. Results: The findings revealed a significant improvement in patient adherence within the intervention group, increasing from 31.12 ± 1.20 to 46.44 ± 1.56, compared to the control group, which only rose from 28.68 ± 1.07 to 33.24 ± 0.97 (p < 0.001). Wound healing outcomes also showed significant differences between groups, where the intervention group’s healing scores improved from 42.32 ± 2.19 to 21.84 ± 2.19, while the control group improved from 42.36 ± 1.87 to 36.48 ± 1.16 (p < 0.001). Conclusion:The implementation of the KMB Digital Education Application significantly enhances patient adherence to wound care and accelerates wound healing among post-abdominal surgery patients. The use of digital education technology can therefore be an effective innovation to support postoperative recovery and improve the quality of nursing care.